Produksi Bionanomineral Selenium Dari Berbagai Jenis Strain Bakteri Asam Laktat (BAL) Sebagai Aditif pada Ransum Ternak Ruminansia - Rizki Amalia Nurfitriani; Roni Ridwan; Anuraga Jayanegara; Nur Rochmah Kumalasari; Santi Ratnakomala; Yantyati Widyastuti (Jurnal Ilmu Peternakan Terapan, 2020)
Mineral absorption in ruminants have not been maximal. This would be seen from the various problems that occur in ruminants, one of which was caused by mineral deficiency, especially the mineral Selenium (Se). Therefore, it was necessary to have applied technology to increase the absorption of Se minerals, one of which was used by bionanomineral technology. The purpose of this study was to determine the production of bionanomineral Se from various types of Lactic Acid Bacteria (LAB) strains. The method used consisted of preparing tools and materials, breeding lactic acid bacteria, making Bionanomineral Se, and observed the production of Bionanomineral Se. The research treatment consisted of 2 stages, namely the first stage consisting of 4 treatments of different LAB strains: TSD 10, SPCE, DR162, and IA2, stage 2 each LAB strains were given treatment doses of 25 ppm and 50 ppm. The parameters observed included Stage 1: Bionanomineral production produced by intracellular and extracellular bacteria, stage 2: Optical Density (OD) and pH. The research design used a quantitative descriptive. The results showed that extracellular bionanomineral production was more than intracellular, the addition of 25 to 50 ppm Se showed that the OD of the four bacterial strains survived, and the pH results varied from each bacterial strain but were still within the normal range. The conclusion of this research was the production of bionanomineral Se as much as 25 ppm and 50 ppm in various types of different LAB strains, would be used as a potential source of organic Se minerals for ruminants.